Silicone Induced Severe Hypercalcemia - K Jayathilaka, Dhammi K (J Endocr Soc, 2021)
Background: Silicone injections are becoming increasingly prevalent for cosmetic enhancement in the transgender population. We report a case of silicone-induced hypercalcemia to highlight the process of extra-renal production of 1,25-hydroxy (OH) vitamin D (calcitriol) and discuss the approaches in managing this rare entity. Clinical Case: A 51-year-old African American transgender female with a past medical history of human immunodeficiency virus (HIV) on antiretroviral therapy with undetectable viral load presented with right flank pain, nausea, and vomiting for one day. On examination, nodules were palpated in both breasts, left lateral hip, and the gluteal area had hyperpigmentation from silicone injections ten years ago. Calcium was elevated at 15.2 mg/dL (8.5–10.5) with albumin 3.8 g/dL (3.5–5), ionized calcium 7.4 mg/dL (4.64–5.28), phosphate 4.5 mg/dL (2.5–4.8) and creatinine of 3.2 mg/dL (0.4–1.4). Imaging revealed right ureteral calculi with hydronephrosis requiring stent placement. PTH was suppressed <5 pg/ml (12–72) and PTHrP were negative. Vitamin D 25 (OH) of 28 ng/mL (30–100) with elevated 1, 25 OH2 D3 144 pg/ml (19–79) and ACE 141 units/L (12–60) were suggestive of a granulomatous process. CT chest and abdomen without contrast did not show any hilar, mediastinal, or abdominal lymphadenopathy to suggest sarcoidosis or lymphoma, but numerous bilateral calcified masses were noted within the breasts consistent with silicone injections. Serum and urine electrophoresis were consistent with monoclonal gammopathy of undetermined significance. Patient deferred further evaluation (PET-CT and skin biopsy for granulomatous changes) as an outpatient. Calcium improved in 4 days to 10.5 mg/dL with intravenous hydration, calcitonin 260 units, IV furosemide 20 mg, and pamidronate of 60 mg. Despite a repeat dose of Pamidronate 60 mg a week later her calcium was rising again to 11.1 mg/dL. Plastic surgery evaluation concluded that due to extensive implants, surgery would be very disfiguring and challenging. She was reluctant to start prednisone as it may affect healing after surgery and the need for antibiotic prophylaxis for HIV, but she later agreed. Prednisone 20 mg daily was started for granulomatous disease and Calcium improved to 10.3 mg/dL. Conclusion/Clinical Lesson: Silicone Induced hypercalcemia is a rare entity with diagnostic and treatment dilemmas. Based on the few reported cases, silicone induced severe hypercalcemia is managed with IV hydration, denosumab, or zoledronic acid. However, glucocorticoids may maintain normocalcemia like in other granulomatous diseases. Removal of silicone implants may improve hypercalcemia, but it is challenging given the extent of implants, disfigurement, and possible disseminated disease and may not be curative. These aspects need to be considered in evaluating and management.